Supervision and Employee Performance: A Case Study of Kigezi Industries Limited in Kabale District. - Ainembabazi, Debrah (Kabale University, 2025)
The purpose of this study was to examine the effect of supervision on employee performance in Kigezi Industries Limited in the Kabale district. The study was guided by the following objectives: to identify the role of supervision on employee performance in Kigezi industries, to identify the employee performance indicators in Kigezi industries, to establish the relationship between supervision and employee performance